Optimizing millennial consumer engagement with mood analysis - Dasgupta, Sabyasachi, 1982-; Grover, Priya, 1974- (Business Science Reference, 2019)
"This book provides an innovating research methodology of mood analysis which will help researchers in conducting similar research in other brands and category not mentioned in this book. It guides marketers to mood elevators and enable them to make consumers purchase their brands"--